How Audit Committee Address The Effects Of Political Connections And Government Ownership In Banking Sector - Rini Dwiyuna Ningsih; Indayani Indayani; Fifi Yusmita (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to examine the influence of political connections, government ownership, and changes in loans on financial performance, as well as the role of the audit committee in moderating the relationship between political connections, government ownership, and financial performance. Methodology/approach: The research sample consists of 32 banking companies listed on the Indonesia Stock Exchange from 2017 to 2021. This study utilizes the Structural Equation Model-Partial Least Squares (SEM-PLS) analysis with WarpPLS.. Findings: The research results indicate that political connections and changes in loans have a significant impact on financial performance, while government ownership does not show any influence on financial performance. Moreover, the audit committee was found to moderate the relationship between political connections and government ownership with financial performance. Practical implications: This research contributes to the management of companies by providing insights into the factors that influence the improvement of the company's financial performance. A significant improvement in financial performance is a positive signal that investors receive about the company, thus influencing their investment decisions. Originality/value: This research adds an audit committee as a moderator, uses market-based measurements for banking financial performance, and uses a new measurement scale to assess the size of companies, especially in the banking sector, referring to POJK. Number 12 of 2021 based on Bank Group Core Capital (KMBI).